Surveillance of high-risk early postsurgical patients for real-time detection of complications using wireless monitoring (SHEPHERD study): results of a randomized multicenter stepped wedge cluster trial - Posthuma, Linda M.; Breteler, Martine J. M.; Lirk, Philipp B.; Nieveen van Dijkum, Els J.; Visscher, Maarten J.; Breel, Jennifer S.; Wensing, Carin A. G. L.; Schenk, Jimmy; Vlaskamp, Lyan B.; van Rossum, Mathilde C.; Ruurda, Jelle P.; Dijkgraaf, Marcel G. W.; et al. (Frontiers in Medicine, 2024)
Background: Vital signs measurements on the ward are performed intermittently. This could lead to failure to rapidly detect patients with deteriorating vital signs and worsens long-term outcome. The aim of this study was to test the hypothesis that continuous wireless monitoring of vital signs on the postsurgical ward improves patient outcome Methods: In this prospective, multicenter, stepped-wedge cluster randomized study, patients in the control group received standard monitoring. The intervention group received continuous wireless monitoring of heart rate, respiratory rate and temperature on top of standard care. Automated alerts indicating vital signs deviation from baseline were sent to ward nurses, triggering the calculation of a full early warning score followed. The primary outcome was the occurrence of new disability three months after surgery Results: The study was terminated early (at 57% inclusion) due to COVID-19 restrictions. Therefore, only descriptive statistics are presented. A total of 747 patients were enrolled in this study and eligible for statistical analyses, 517 patients in the control group and 230 patients in the intervention group, the latter only from one hospital. New disability at three months after surgery occurred in 43.7% in the control group and in 39.1% in the intervention group (absolute difference 4.6%) Conclusions: This is the largest randomized controlled trial investigating continuous wireless monitoring in postoperative patients. While patients in the intervention group seemed to experience less (new) disability than patients in the control group, results remain inconclusive with regard to postoperative patient outcome due to premature study termination. Trial registration: ClinicalTrials.gov; ID:NCT02957825. Funding: Amsterdam University Medical Center